2016
DOI: 10.3389/fpls.2015.01199
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing, De novo Assembly, Functional Annotation and Analysis of Phyllanthus amarus Leaf Transcriptome Using the Illumina Platform

Abstract: Phyllanthus amarus Schum. and Thonn., a widely distributed annual medicinal herb has a long history of use in the traditional system of medicine for over 2000 years. However, the lack of genomic data for P. amarus, a non-model organism hinders research at the molecular level. In the present study, high-throughput sequencing technology has been employed to enhance better understanding of this herb and provide comprehensive genomic information for future work. Here P. amarus leaf transcriptome was sequenced usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 86 publications
(83 reference statements)
10
10
0
Order By: Relevance
“…Genome-wide SSR analyses in nine species of the Poaceae family [82] revealed that the most abundant repeat type was a hexamer (58.82%). Conversely, our results were consistent with those obtained in licorice ( Glycyrrhiza uralensis ) in which the most frequent repeat motif was a mono-nucleotide, followed by tri-nucleotides and di-nucleotide motifs [83], and partially to those obtained in bhumyamalaki ( Phyllanthus amarus ), in which the most abundant repeat type was a mono-nucleotide, followed by di- and tri-nucleotides [84]. Although natural genetic variation in A. donax was reported to be low for the Mediterranean basin and slightly higher for the Asian area [85], and genetic uniformity was also observed in ecotypes in the United States [86], here 53 Candidate PolySSRs were predicted using CandiSSR software, suggesting a likely high level of genetic diversity among the analyzed ecotypes.…”
Section: Discussionsupporting
confidence: 90%
“…Genome-wide SSR analyses in nine species of the Poaceae family [82] revealed that the most abundant repeat type was a hexamer (58.82%). Conversely, our results were consistent with those obtained in licorice ( Glycyrrhiza uralensis ) in which the most frequent repeat motif was a mono-nucleotide, followed by tri-nucleotides and di-nucleotide motifs [83], and partially to those obtained in bhumyamalaki ( Phyllanthus amarus ), in which the most abundant repeat type was a mono-nucleotide, followed by di- and tri-nucleotides [84]. Although natural genetic variation in A. donax was reported to be low for the Mediterranean basin and slightly higher for the Asian area [85], and genetic uniformity was also observed in ecotypes in the United States [86], here 53 Candidate PolySSRs were predicted using CandiSSR software, suggesting a likely high level of genetic diversity among the analyzed ecotypes.…”
Section: Discussionsupporting
confidence: 90%
“…In present study, multiple transcripts which encoded some of the known enzymes participated in the MVA pathway and the saponin biosynthesis pathway were found in traditional herbs, e.g., Panax ginseng (Cao et al, 2015), Phyllanthus amarus (Mazumdar and Chattopadhyay, 2016), Panax japonicus (Rai et al, 2016), Astragalus membranaceus Bge (Chen et al, 2015), and Eleutherococcus senticosus (Hwang et al, 2015). Genes involved in the MVA pathway in the A. bidentata transcriptome included 3-hydroxy-3-methylglutaryl CoA synthase (HMGS), HMG-CoA reductase (HMGR), phosphomevalonate kinase (PMK), mevalonate-5-diphosphate decarboxylase (MDD), isopentenyl diphosphate isomerase (IDI), geranyl diphosphate synthase (GPPS), farnesyl diphosphate synthase (FPS), geranylgeranyl diphosphate synthase (GGPPS), squalene synthase (SS), squalene epoxidase(SE), beta-amyrin synthase (β-AS), and CAS.…”
Section: Resultsmentioning
confidence: 77%
“…WEGO (http://wego.genomics.org.cn/cgi-bin/wego/index.pl) was used to functionally classify the target genes and graphically represent the target gene functions (Mazumdar & Chattopadhyay, ). It is a useful tool for plotting GO annotation results and shows the categorization into three main ontologies: “cellular component,” “molecular function’,” and “biological process.”…”
Section: Methodsmentioning
confidence: 99%
“…WEGO (http://wego.genomics.org.cn/cgi-bin/wego/index.pl) was used to functionally classify the target genes and graphically represent the target gene functions (Mazumdar & Chattopadhyay, 2016).…”
Section: Function Classification Of the Target Genes Of Differentiamentioning
confidence: 99%